الحاجات المعرفية لمرضى السرطان وذويهم واتجاهاتهم حول المعالجة الكيماوية - غزال سوسن (Latakia University Journal -Medical Sciences Series, 2019)
مقدمة: في هذه الدراسة قُوِّمت معلومات المرضى المصابين بالسرطان المعالجين كيماويا وذويهم واتجاهاتهم، وشملت الدراسة المرضى المقبولين في مركز الأورام في مشفى تشرين الجامعي في محافظة اللاذقية بين 1-5-2008 ولغاية 15-1-2009. المناهج: اختير 40 مريضاً مصابون بالسرطان ويعالجون معالجة كيماوية، وذلك بطريقة عشوائية بسيطة. قابلت الباحثة جميع المرضى وملأت استمارة الأسئلة. النتائج: كان مستوى المعرفة جيداً لدى 35% من المرضى, بينما كانت الاتجاهات إيجابية لدى 30 % منهم. كما كان مستوى المعرفة جيداً لدى 30% من ذوي المرضى, بينما كانت الاتجاهات إيجابية لدى 30 % منهم. كان مصدر معلومات المريض كالتالي: 5% الطاقم التمريضي, 10 % الطاقم الطبي, 85 % من مصدر ذاتي (55% تلفزيون, 20%مجلات, 10% محاضرات تثقيفية ومجلات). الاستنتاجات: ظهر من خلال النتائج أنه لا يوجد تثقيف فعال للمرضى حول العلاج الكيميائي واختلاطاته وذلك من خلال تدني مستوى المعرفة والاتجاهات للمرضى وذويهم. وبالتالي هناك حاجة ماسة لبرامج تثقيفية لهؤلاء المرضى وذويهم وذلك لتحسين القدرات والمهارات للمرضى وذويهم للتأقلم مع العلاج الكيماوي وتأثيراته الجانبية. Background: In this study, we evaluated the knowledge and attitudes of the patients with cancer admitted to the center of chemotherapy in Tishreen Hospital, Lattakia, in 2008 toward chemotherapy. Methods: Forty patients suffering different types of cancer and undergoing chemotherapy were selected with a simple random sampling method. All were interviewed and a questionnaire was completed for each by the researcher. Results: The level of knowledge was good in 35% of patients, and attitude was positive in 30% of them. The level of knowledge was good in 30% of patient’s families, and attitude was positive in 30% of them. The sources of patients’ information were as follows: 5 % by the nurses, 10 % by the physicians, and 85% by themselves (55% T.V, 20% family, 10% lecture and journals). Conclusion: According to the results, it seems that unfortunately, there is not effective education about chemotherapy complication, because their knowledge and attitude were not at an acceptable level. An educational program is needed for patients to improve their ability and skills for coping wit chemotherapy and its side effect as well as adapting to the illness.